2021
DOI: 10.1590/0366-69132021673833118
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing concrete with crystalline admixture made with different cement content

Abstract: Self-healing concrete (SHC) is obtained with self-healing agents, which can seal small cracks without additional repair works, improving concrete durability. The present paper studied the influence of cement content (450, 475, and 500 kg/m 3 ) on mechanical properties (compressive and tensile strength) and porosity (capillary water absorption, water absorption, and void index) of SHC with crystalline admixture. A crack induction was carried out in SHC, and the results were compared with two reference concretes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
4
0
4
Order By: Relevance
“…In addition, it was also found that the admixture had no effect on the air content or density of the concrete. On the contrary, Geraldo et al [12] saw the addition of a crystalline admixture, not specified, resulting in reduced slump. This may be attributed to the mixture design as the water to binder ratio was quite high.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it was also found that the admixture had no effect on the air content or density of the concrete. On the contrary, Geraldo et al [12] saw the addition of a crystalline admixture, not specified, resulting in reduced slump. This may be attributed to the mixture design as the water to binder ratio was quite high.…”
Section: Discussionmentioning
confidence: 96%
“…Another method of self-healing that has been discussed is the use of different types of admixtures, including mineral or crystalline in creating self-healing concrete. [4,5,7,8,9,10,[11][12][13][14][15][16][17][18][19][20] With crystalline admixtures, the process requires moisture because the CO2 present in it reacts with calcium ions (Ca 2+ ) in the concrete to form calcium carbonate (CaCO3) which starts to fill the cracks and heal the concrete. The healing capability this promotes is for cracks up to 300 µm in width.…”
Section: Introductionmentioning
confidence: 99%
“…As amostras destinadas ao ensaio de absorção de água por capilaridade retornaram à cura submersa após o ensaio, permanecendo nessa condição até a idade de 76 dias, quando a capacidade de absorção de água foi novamente avaliada. O retorno das amostras para a cura submersa pode contribuir-para uma maior eficácia da autocicatrização por grãos anidros, intensificando a possibilidade de hidratação ou cristalização contínua dos aditivos cristalinos no processo de autorreparação [5,37]. Os aditivos cristalinos precisam ter acesso a água para o desencadeamento do seu processo químico, promovendo a lixiviação do hidróxido de cálcio do interior da fissura para a superfície, intensificando a formação de carbonato de cálcio [24,38].…”
Section: Pré-carregamento Dos Concretosunclassified
“…Segundo a autora, isso se deve ao fato de que os cimentos de alta resistência inicial já apresentam cerca de 82% da resistência exercida aos 28 dias, já nas fases iniciais. AZARSA et al [18], GERALDO et al [37] e PAZDERKA e HÁJKOVÁ [45] examinaram o impacto do uso de 2% de teor de aditivo cristalino no processo de autocura. Com exceção de PAZDERKA e HÁJKOVÁ [45] no qual não observaram um aumento significativo na resistência à compressão dos concretos analisados aos 28 dias, AZARSA et al [18] e GERALDO et al [37] mostraram que a resistência à compressão axial aos 28 dias das amostras que continham CA, após o período de cura, apresentaram um impacto significativo na recuperação da resistência mecânica.…”
Section: Resistência à Compressão Axialunclassified
“…In using crystalline admixtures, its nature as water-resistant and permeability-reducing [12] hints at an ability to sustain a lower water absorption rate; this has been established in various experiments with different components of the admixture [18,19,[33][34][35]. However, in the use of crystalline admixtures, there is a lack of comparability in research [16,17] due to nonlinearity in admixture composition and testing methods [12,16], this hinders understanding its feasibility in relation to comparably well-documented performance of bacterial SHC.…”
Section: Durability Propertiesmentioning
confidence: 99%